A novel CMOS low-noise amplifier design for 3.1-to 10.6-GHz ultra-wide-band wireless receivers - Ma, Jianguo (2009)
An ultra-wideband (UWB) 3.1- to 10.6-GHz low-noise amplifier (LNA) employing a common-gate stage for wideband input matching is presented in this paper. Designed in a commercial 0.18-um 1.8-V standard RFCMOS technology, the proposed UWB LNA achieves fully on-chip circuit implementation, contributing to the realization of a single-chip CMOS UWB receiver.